Nutrtional Quality of Fermented Spray Dried Medida Formulated From Malted Brown Rice with Bifidobacterium Longum BB 536 - Mohammed Kabeir, Barka (2004)
The processing technique of medida, the traditional Sudanese porridge was modified to improve the nutritional quality. The paddy rice was steeped and malted at 30 ˚C. Medida was formulated using 225 g brown rice flour of two days malted paddy with added skim milk at 2.25 %, 4.5% and 10% levels (W/V) were studied. The initial pH was 6.7 and fermentation was run to a final pH of 4.4 using culture of Bifidobacterium longum BB 536. Fermented Medida containing B. longum BB 536 cell counts up 9 Log CFU/ ml was spray dried at different heat adaptations and spray drying air outlet temperatures with fixed inlet temperature of 160 ˚C.